Russia's Transition to a New Federalism - Martinez-Vasquez, Jorge; Boex, Jameson (Washington, DC: World Bank, 2013)
In the preface to this report, it is asserted that, "history hovers... over any discussion of fiscal federalism in Russia." This report not only reviews that history, but also follows it to the present situation with respect to the difficult policy choices facing the new Putin-led government, and neatly links Russia's choices with the broader issues facing any country undergoing intergovernmental reform. Thus, the authors weave into the discussion the dynamics of Russia's options with respect to deciding who delivers what services and how to finance these services with the question of the fiscal politics of change, or the intergovernmental and inter-regional balancing and counterbalancing of power. Furthermore the authors tie these questions together with those of how to implement good governance: should it be piecemeal or unified, asymmetric or uniform, and centrally driven or locally controlled? This report also initiates the first in a series of studies that will be published in the World Bank Institute's Learning Resource Series on the issues of governance and decentralization as they are framed by the WBI's broader set of programs in public finance and financial management.